Effectiveness of Patrols by the Karanganyar Police Samapta Unit in Realizing Public Security and Order - Farrel Leondy (Tanggon Kosala, 2022)
The National Police is a law enforcement institution that is directly under the President, however law enforcement is often harmed by elements from within the Police who have a tendency to deviate and are irresponsible. This has resulted in the performance of the police being ineffective and not running as it should. There were several deviant acts committed by members of the police, such as delaying the implementation of patrols so that activities did not go according to the activity plan and the results obtained were not as expected. This also happened at the Karanganyar Police Station. Researchers used a qualitative approach to the type of research field research. The sources obtained are from primary and secondary data sources. Data collection was carried out by interview, observation, and document study techniques. The research focuses on the Karanganyar Police Samapta Unit. The validity of the data using the triangulation method. Data analysis with interactive models through data reduction, data presentation, as well as conclusions and data verification. The results of the study show that the activities carried out in preventing criminal acts have not been effective, both in terms of the elements of man, money, material, method, and machine. In addition, there are problems in the stages of implementation both in planning, organizing, actuating, and supervising. Actions taken to increase the effectiveness of preventing criminal acts at the Karanganyar Police Station were carried out by evaluating patrol activities from the Karanganyar Police Samapta Unit.